Phytoprostane and phenolic compounds from Chromolaena palmaris. Issue 20 (13th October 2022) - Souza, Mariana R. Passos de; Ramos, Anderson V. G.; Oliveira, Josiane A. Monteiro de; Cabral, Márcia R. P.; Sampiron, Eloísa G.; Scodro, Regiane B. de Lima; Foglio, Mary Ann; Ruiz, Ana Lucia T. G.; Carmo, Marta R. B. do; Sarragiotto, Maria H.; Baldoqui, Debora C.
Abstract: The chemical investigation of Chromolaena palmaris (Sch.Bip . ex Baker) R.M. King & H. Rob. expands the phytochemical composition knowledge of Chromolaena genus, since this is the first chemical investigation of this species. Twenty-five compounds were identified, including a phytoprostane, 17 flavonoids, 6 phenolic acids, and a caffeoyl-glucoside derivative obtained by classical chromatography and UHPLC-HRMS/MS analysis. Moreover, anti- Mycobacterium tuberculosis and antiproliferative activities of C. palmaris were evaluated. Dichloromethane fraction showed cytotoxicity towards human cancer cell lines, presenting TGI values on glioma (U251) of 27.8 μg mL −1 . Furthermore, compounds 1 and 2 exhibited antimicrobial activity against Mycobacterium tuberculosis with MIC of 62.5 and 15.6 μg mL −1, respectively. GRAPHICAL ABSTRACT: UF0001